Tunneling Glashow-Weinberg-Salam Model Particles from Black Hole Solutions in Rastall Theory - Övgün, Ali; Javed, Wajiha; Ali, Riasat (Hindawi Ltd, 2018)
Using the semiclassical WKB approximation and Hamilton-Jacobi method, we solve an equation of motion for the Glashow-Weinberg-Salam model, which is important for understanding the unified gauge-theory of weak and electromagnetic interactions. We calculate the tunneling rate of the massive charged W-bosons in a background of electromagnetic field to investigate the Hawking temperature of black holes surrounded by perfect fluid in Rastall theory. Then, we study the quantum gravity effects on the generalized Proca equation with generalized uncertainty principle (GUP) on this background. We show that quantum gravity effects leave the remnants on the Hawking temperature and the Hawking radiation becomes nonthermal.
Keywords: Generalized Uncertainty Principle; Hawking Radiation; Quantum-Gravity; Minimal Length; Kerr; Temperature; Rindler